Tata Kelola Keuangan untuk Meningkatkan Efektivitas dan Efisiensi Pelaku UMKM Desa Girikerto, Sleman, Daerah Istimewa Yogyakarta, Tahun 2023 - Elma Vania Rahmawati; Muhammad Nuur Farid Thoha (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study was conducted to determine financial management training to improve effectiveness and efficiency using the Ngecash.id website in Micro, Small, and Medium Enterprises (MSMEs) located in Girikerto Village, Sleman. In this study, data sources were obtained from primary data and secondary data. Data were analyzed using descriptive analysis methods. The conclusion of this study is to conduct training on financial management for MSME actors in increasing knowledge digitally through the Ngecash.id website with the output produced in the form of payment receipts or Bills and recording sales reports.